2022
DOI: 10.1021/jasms.1c00329
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Plasma-Based Medium Pressure Chemical Ionization Source for GC-TOFMS

Abstract: The construction, critical evaluation, and performance assessment of a medium-pressure (2–13 mbar), high-temperature chemical ionization (CI) source for application in GC-MS is described. The ion source is coupled to a commercial time-of-flight (TOF) mass analyzer. Reagent ions are generated in a two staged process. The first stage uses a filament free, helical resonator plasma (HRP) driven ion source for H3 + generation. Reagent gases, for example, nitrogen, isobutane, and methane are added in a second stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Details on the custom CI source in combination with a GC-TOF were presented previously. 29 Both sources operate continuously. A custom ion optical device consecutively extracts the ion populations from each source and pulses them into the TOF analyzer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details on the custom CI source in combination with a GC-TOF were presented previously. 29 Both sources operate continuously. A custom ion optical device consecutively extracts the ion populations from each source and pulses them into the TOF analyzer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The EI source was operated with 70 eV electron energy and an emission current of 1 mA. Details on the custom CI source in combination with a GC-TOF were presented previously …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [19], the selectivity was altered by adding different reagent gases such as nitrogen, methane, and isobutane directly into the second stage of the CI source. In this study, however, a main flow of nitrogen enriched with dopants such as water or ammonia provided by a reagent gas supply unit is used for reagent variation as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma-based CI source used in combination with the EI source was presented earlier. 19 Low hydrogen flow rates obtained from a small and laboratory-safe on-demand generator are used for ion generation. Earlier it was shown that the primarily generated H 3 + population can be specifically converted to a variety of other reagent ions, e.g., [N 2 H] + /[N 4 H] + , [H 3 O] + , or [C 4 H 9 ] + , which enables the adjustment of the gas phase acidity and consequently balance between selectivity and the degree of fragmentation.…”
mentioning
confidence: 99%